Guided Reading-Thinking (PPP): A Method for Teaching Asian Literature - Lagat, Susan (International Journal of Arts, Sciences and Education, 2021)
One of the requirements of the new curriculum is the development of learning skills such as reading comprehension for 21st century students. This study was created to keep up with and follow the call of the modern trend in pedagogy or teaching in the Filipino subject, particularly in Asian Literature subjects. This study focuses on looking at the Guided Reading-Thinking strategy, as an effective method of teacher instruction and students' understanding of reading Asian literature to respond to the call of 21st century skills. How can Guided Reading-Thinking respond to the call for 21st-century skill needs, and what impact does this have on teachers' pedagogy and student learning? The research design used in the study is qualitative because the main objective of the study was to establish answers to the hows of the action research questions. The findings revealed that, based on the posttest results, there was an increase in the score of the experimental group while the level of the control group remained the same. Keywords: Guided Reading -Thinking learning skills modern trend pedagogy 21st century skills